Ban Gu: copyist, creator and critic. (June 2015) - Loewe, Michael
Abstract Ban Gu's compilation of the Han shu may be seen in the context of a number of intellectual and religious developments. By his time the idea of the Tian ming and the theory of the Wu xing were being applied to imperial times. Officials were quoting the sayings of Kongzi to support their arguments, and the writings of distinguished scholars such as Jing Fang, Liu Xiang, Liu Xin and Yang Xiong were well known. The religious controversies that had begun in the reign of Chengdi had died down. The pursuit of scholarship had received a new impetus thanks partly to the discussions held in 79 ce. Ban Gu drew somewhat freely on existing literature, being prudent to select material that would not arouse enmity; his sister called on official documents to complete her part of the history. As an innovator Ban Gu introduced chapters on subjects that had not been treated in the Shi ji, such as bibliography and the laws. Ready to criticize the actions of officials or the character of an emperor openly, he also contrived to do so implicitly.